2010
DOI: 10.1038/nrrheum.2010.154
|View full text |Cite
|
Sign up to set email alerts
|

The Japanese experience with biologic therapies for rheumatoid arthritis

Abstract: The unique genetic, environmental and medical backgrounds of people in Japan might influence the effectiveness and safety of biologic agents in patients with rheumatoid arthritis (RA). Indeed, clinical trials revealed higher response rates to some biologic agents (including infliximab, etanercept and tocilizumab) in patients with RA in Japan than patients treated with the same agents in Western countries, although response rates to adalimumab were comparable in both populations. The reasons why response rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 100 publications
(49 citation statements)
references
References 59 publications
2
46
1
Order By: Relevance
“…Regarding medication differences there was, for example, no direct comparison of high and low MTX doses between this Japanese study and the global tofacitinib studies. Differences in efficacy responses between Japanese and Western populations have also been observed in clinical trials of biologic DMARDs, including infliximab, etanercept, and tocilizumab (reviewed extensively by Takeuchi and Kameda [17]). Alternatively, these observations could be due to differences in MTX dosing.…”
Section: Discussionmentioning
confidence: 90%
“…Regarding medication differences there was, for example, no direct comparison of high and low MTX doses between this Japanese study and the global tofacitinib studies. Differences in efficacy responses between Japanese and Western populations have also been observed in clinical trials of biologic DMARDs, including infliximab, etanercept, and tocilizumab (reviewed extensively by Takeuchi and Kameda [17]). Alternatively, these observations could be due to differences in MTX dosing.…”
Section: Discussionmentioning
confidence: 90%
“…Importantly, they typically developed AoDILD within several months of successful biological treatment in addition to MTX and low-dose glucocorticoids. TNF inhibitors infliximab and etanercept were the predominant biological agents, chiefly because both adalimumab and tocilizumab had only been approved in Japan for RA in April 2008 (19), and no patients treated with adalimumab were found in the present study.…”
Section: Pcp Is the First Choice Of Diagnosis For Aodild In Ra Patienmentioning
confidence: 63%
“…Clinical trials revealed higher response rates to some biologics including infliximab, etanercept and tocilizumab 16) . Treatment guidelines for TNF-α blocking agents in Japan were firstly published by JCR in 2005 17) .…”
Section: Biological Agents and Their Postmarketing Surveillance (Pms)mentioning
confidence: 99%